2007
DOI: 10.1002/jcc.20797
|View full text |Cite
|
Sign up to set email alerts
|

McLafferty rearrangement of the radical cations of butanal and 3‐fluorobutanal: A theoretical investigation of the concerted and stepwise mechanisms

Abstract: The stepwise and concerted pathways for the McLafferty rearrangement of the radical cations of butanal (Bu(+)) and 3-fluorobutanal (3F-Bu(+)) are investigated with density functional theory (DFT) and ab initio methods in conjunction with the 6-311+G(d,p) basis set. A concerted transition structure (TS) for Bu(+), (H), is located with a Gibbs barrier height of 37.7 kcal/mol as computed with CCSD(T)//BHandHLYP. Three pathways for the stepwise rearrangement of Bu(+) have been located, which are all found to invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…And the last step of the electron transfer, in fact, has a high energy barrier of 36 kcal/mol. It also should be mentioned that similar processes of electron transfers inside ion–neutral complexes were also previously reported by other research groups. , …”
Section: Resultssupporting
confidence: 85%
“…And the last step of the electron transfer, in fact, has a high energy barrier of 36 kcal/mol. It also should be mentioned that similar processes of electron transfers inside ion–neutral complexes were also previously reported by other research groups. , …”
Section: Resultssupporting
confidence: 85%
“…In support, the corresponding fragmentation of isopropyl and npropyl esters is very similar. In a theoretical study of the McL1H rearrangement, 17 an activation energy of &0.1 eV has been calculated for comparable complexes as intermediates for a stepwise mechanism.…”
Section: Benzoic Acid Isopropyl Estermentioning
confidence: 99%
“…However, the detailed mechanism is still under debate between a concerted and a stepwise mechanism via formation of an intermediate distonic ion [6][7][8] by g-hydrogen shift and subsequent homolytic C-C bond cleavage to yield uncoordinated free products. The stepwise mechanism is strongly favored, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] mainly based on arguments concerning the lifetime of intermediates 12 and the competitive H/D exchange in some isotopically labelled ketones prior to the C-C bond cleavage, depending on the stability of the intermediate distonic ion with branched and straight aliphatic chains 13 or the product stability. 14 An extension of the last step assumes the formation of an ion/molecule complex as intermediate for the products but also for intra-cage reactions like hydrogen scrambling or a further hydrogen transfer.…”
Section: Introductionmentioning
confidence: 99%
“… The study of the major MS fragmentations of these carbonyl derivatives, however, has not received due attention. For example, although the McLafferty rearrangement of carbonyl compounds has been the focus of extensive and continuous research , studies on oximes and silyl oxime ethers have been limited. Surprisingly, to date, only one article has reported the McLafferty rearrangement for ketoximes.…”
Section: Introductionmentioning
confidence: 99%
“…[33,39,42,53,57] Various theoretical studies have been performed that confirmed the stepwise mechanism, but some also identified systems that should or could proceed through the concerted mechanism. [23,38,40,48,65] Finally, in addition to the single hydrogen transfer McLafferty rearrangement, consecutive rearrangements that proceed by a double hydrogen transfer have been reported. [29] In general, one would expect that the McLafferty rearrangement will have to compete with other fragmentation pathways, such as simple bond cleavages that are entropically more favorable.…”
Section: Introductionmentioning
confidence: 99%